DISCRETE EVENT SIMULATION IN THE HIGH SCHOOL PHYSICAL EDUCATION: APPLICATION IN REFRACTION AND REFLECTION OF LIGHT - DO NASCIMENTO, JANAINA RIBEIRO; Rangel, Joao Jose de Assis; FILHO, MILTON BAPTISTA (Brazilian Journal of Operations & Production Management, 2014)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –> This paper describes the application of a model of discrete event simulation (DES) to be used as a teaching resource in the classroom. Some basic concepts of physics related to refraction and reflection of light, typically taught in high school classes were simulated. A comparison of some relevant aspects, relating the simulation models developed in this work with other existing of similar purpose, was held. As a result, it was found that the models built for this work, besides not requiring large resources of laboratory, demonstrate as significant advantages the dynamic visualization of concepts to be taught, the possibility of adaptation to new parameters, in addition to be built in time relatively short.